PROBLEM SOLVING AND ALTERNATIVE SELECTION TO IMPROVE GASSY WELL AT PETKO FIELD BY USING DECISION ANALYSIS - Syukron, Muhammad
WK Rokan is the most productive oil block in the history of Indonesia’s oil and gas, has more than 12 thousand active oil wells scattered in more than 100 active fields operating and contributes around 23.5% of national oil production. One of the active fields in WK Rokan is the Petko field which has around 400 production wells with a production of nearly 17,000 Barrels Oil Per Day (BOPD).